Measuring tactical behaviour in football - Sampaio, J.; Macas, V. (International Journal of Sports Medicine, 2012)
The present study explored how football players' dynamic positional data can be used to assess tactical behaviour by measuring movement patterns and inter-player coordination. A pre post-test design was used to assess the effects of a 13-week constructivist and cognitivist training program by measuring behaviour in a 5×5 football small-sided game, played on a 60×40 m outdoor natural turf pitch. Data was captured at 5 Hz by GPS devices (SPI Pro, GPSports, Canberra, Australia) and analysed with non-linear signal processing methods. Approximate entropy values were lower in post-test situations suggesting that these time series became more regular with increasing expertise in football. Relative phase post-test values showed frequent periods with a clear trend to moving in anti-phase, as measured by players' distance to the centre of the team. These advances may open new research topics under the tactical scope and allow narrowing the gap between sports sciences and sports coaching.